Lomba Pembuatan Mini Garden dan Pembenahan Ujung Gang Di Kelurahan Cawang Jakarta Timur - Margareta Maria Sudarwani; Sri Pare Eni; Galuh Widati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The current situation of the Cawang Sub-District which is our partner, like most settlements during the Covid 19 pandemic era, is to continue to maintain a new normal environment that is healthy and balanced. The community Service Team of Architecture of Engineering Faculty UKI hopes to play a real role in overcoming existing problems to optimally improve the function of a healthy residential environment. Therefore, one of the solutions to overcome the problem is to keep pushing to create a clean, healthy environment free of waste. In the era of the COVID-19 Pandemic, the people of the Cawang Sub-District, East Jakarta, have started to stretch their activities outside the home. As before the COVID-19 era, PKK women in the Cawang sub-district of East Jakarta City were active in various activities including environmental health maintenance activities and other PKK activities. For this reason, in the Community Service activities in the Cawang green village development program, we from UKI Architecture, fulfill the request of the Cawang community, to work together in revitalizing community members to be more intense in protecting the environment. The Community Service Program entitled Mini Garden Contest and Senggol Alley Improvement is an effort to prepare a new normal environment in Cawang Village, East Jakarta, in the form of outreach and competitions. Keywords: the end of Senggol Alley; mini garden contest; alley improvement